Pengaruh Terapi Bermain Origami terhadap Tingkat Kecemasan pada Anak Prasekolah dengan Hospitalisasi di Ruang Aster RSD dr. Soebandi Jember (The Effect of Origami Play Therapy toward Anxiety Level on Preschool Age Children Hospitalization in Aster’s Room - Ririn Halimatus Sa`diah; Ratna Sari Hardiani; Rondhianto Rondhianto (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Hospitalization can cause anxiety to preschool children due to separation, lossing of control,injury and pain of body. Origami play therapy aims to minimize anxiety in preschool childrenduring hospitalization. This reasearch was intended to analyze the effect of origami play therapytoward Anxiety Level on Preschool Age Children Hospitalization In Aster’s Room of RSD dr.Soebandi Jember. This research used design approach quasy experiment with non equivalentcontrol group design. Sampling technique used quota sampling with a sample size of 30respondents divided into 2 goups. Research was conducted in Aster’s Room RSD dr. SoebandiJember. Research instrument used anxiety questionnaire modification RCMAS. Analysis of thedata used statistical test of Mann Whitney U test & Wilcoxon match pair test with 95% of CI.The research result showed that p value of Wilcoxon match pair test in experimental group was0,001 and 0,157 in control group, while by Mann Whitney obtained p value of 0,001 (p < α ; α =0,05). It can be concluded that there was an effect of Origami Play Therapy for Anxiety Level onPreschool Age Children With Hospitalization In Aster’s Room dr. Soebandi Jember. It issugested that nurses can provide origami play therapy to minimize or remove anxiety topreschool children during hospitalization.Keywords: Hospitalization, Anxiety, Origami play therapy